Welding - Farnsworth, Steven Robert (--For dummies., 2022)
"This ... practical guide takes you from evaluating the material to be welded all the way through the step-by-step welding process, and everything in between. Plus, you'll get ... guidance on how to apply finishing techniques and advice on how to adhere to safety procedures. Explains each type of welding, including stick, tig, mig, and fluxcore welding, as well as oxyfuel cutting, which receives sparse coverage in other books on welding: tips on the best welding technique to choose for a specific project; and required training and certification information"--Provided by publisher